Dinamisme kewangan Islam Malaysia ([Kuala Lumpur] Akademi Pengajian Islam, Universiti Malaya Penerbit Universiti Malaya, 2006)
Issues on the implementation of Islamic financial system in Malaysia; collection of articles.
Includes bibliographical references.
Keywords: Banks and banking -- Religious aspects -- Islam; Banks and banking -- Malaysia; Finance -- Religious aspects -- Islam; Finance -- Malaysia